Concept of Tributalism: a comparative Analysis of S. Amin 's, J. Haldon's and H. H. Stahl's approaches - Nerijus Babinskas (Lietuvos Istorijos Studijos)
By this article, the author wants to revive discussion about Marxist schemas of social development and their applicability for constructing models of universal history. There are attitudes of three scholars presented in the current text: Samir Amin, who is known in the Western historiographical tradition as a main creator and promoter of the concept of the tributary mode of production; John Haldon, who paid quite much attention to the mentioned concept and dedicated his entire book to this issue; and Henri H. Stahl, who created an original alternative approach to the issue of tributalism.